Assessing the Effectiveness of Single-Session Therapy (SST) on Couples' Mental Health: An Explanatory Mixed-Method Study - Behrouznia, Helia; Madani, Yaser; Salehi, Keyvan; Shahmoradi, Somayeh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study employed an aims to evaluate the effectiveness of SST in enhancing the mental health of couples.Methods: In the quantitative section of this explanatory mixed-method design, a quasi-experimental pretest-posttest design with a control group was utilized. The Mental Health Inventory-28 (MHI-28) by Basharat (2009) was employed to assess couples' mental health before and after the intervention. Data analysis was performed using SPSS22 software, and the findings indicated that SST significantly improved couples' mental health. In the qualitative section, semi-structured interviews were conducted with couples to examine their experiences with this type of therapy through descriptive phenomenology.Findings: According to the eta coefficient, SST accounted for 34% of the variance in the psychological well-being subscale and 17% in the psychological distress subscale, indicating large and medium effect sizes, respectively. The qualitative findings supported the quantitative results, highlighting positive changes such as improved emotional state, increased interest in life, a sense of calmness, feeling loved, hope for the future, and reduced stress and distress one month after the session. These changes aligned with the subscales and questions of the mental health questionnaire, serving as confirmation of the quantitative outcomes.Conclusion: Ultimately, this study emphasizes the importance of SST as an effective therapeutic tool for couples. The findings may be valuable for therapists and future researchers while encouraging clients to seek therapy.